Economic Feasibility of a Compressed Air Energy Storage System Under Market Uncertainty: A Real Options Approach. (May 2017) - Hammann, Eide; Madlener, Reinhard; Hilgers, Christoph
Abstract: Since the liberalization of electricity markets power prices are considered as highly volatile. Thus investment in new power plants is exposed to higher risks. Traditional capital budgeting methods lack the integration of flexibility. This can be overcome by applying real options analysis. In the context of an increasing electricity production by highly volatile renewable power plants, new solutions need to be found to ensure security of supply and to accommodate intermittent generation. Energy storage is seen as a possible solution. The Compressed Air Energy Storage (CAES) technology provides many key features that are relevant to deal with arising problems by renewables. Lately an advanced adiabatic version with higher roundtrip efficiencies has been discussed. However, high capital expenditures limit the economically viable implementation. As conventional CAES uses natural gas for production, it is exposed to price fluctuations on two markets. Depending on the configuration of component sizes, CAES storage units can be used for different purposes. A price model is set up to produce, in combination with the application of a Monte Carlo simulation, possible future price paths for power, natural gas and demand rate for minute reserve. Based on these price paths costs and revenues for different CAES applications are calculated. For the economic evaluation three different configurations are considered for both diabatic and adiabatic CAES. Investment in a diabatic CAES used for load-leveling purposes is found to be the most economical option.